Measurement of Customer Behavior Regarding Coca-Cola and Pepsi: A Study of Hisar City: Understanding consumer behavior in the soft drink market: A case study of Hisar City (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study of consumer behavior involves trying to understand complex human beings and the reasons they act the way they do in the marketplace. It recognizes that consumer decisions take place inside a person who is distinctive in his personality and attitudes, yet similar to other consumers who have been exposed to the same external influences of culture and society. Rather than ignoring these complexities, real estate researchers should embrace the study of consumer behavior to better understand the reasons behind market choices. The present study is based on primary data with 100 respondents using soft drinks. The study is exploratory cum descriptive.